Shodhana Karma: A Holistic Approach to Sthana Roga (International Journal of Ayurveda and Pharma Research, 2024)
The strength of a nation is deeply rooted in the health of its women, making it fundamental step towards national prosperity. Apart from undergoing natural processes of menstruation, pregnancy etc. Sthana Roga is a common condition seen in a woman comprising of lump or palpable mass in the breast. It is computed that about 30% of women are suffering from benign tumors of breast at any age and if not addressed on proper time it may have risk of malignancy. Methods: A case report of a female aged 46-years presented with the complaints of lump with tenderness in the breast it was diagnosed as Sthana Roga. Based on Nidana Panchaka, Chikista was planned and Shodhana Karma was done based on Ayurvedic principles to manage the Sthana Roga. Results: Shodhana Karma led to significant improvement in overall patient’s condition by notable decrease in discomfort, pain, tenderness, reduction in the size of the lump pertaining to the disease and was assessed through necessary investigations. Conclusion: As per this case study, the efficacy of age old Ayurvedic treatment modalities has demonstrated its effectiveness in managing symptoms of Sthana Roga which was confirmed by the investigations before and after the treatment.